DEVELOPMENT OF MOCHI DAIFUKU BUSINESS USING BUSINESS MODEL CANVAS (BMC) METHOD IN BEKASI REGENCY - Varah Fajrin Vebrianty; Rahmah, Zahra Farida; Krisna, Bayu; Setyaningrum, Retno Purwani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to develop the business model of Mochi Daifuku in Bekasi Regency using the Business Model Canvas (BMC) approach. MSMEs significantly contribute to Indonesia’s economic growth, particularly in the food sector, which is favored by many new entrepreneurs. The research method used is a qualitative approach with a descriptive technique. Data were collected through observation, interviews, and questionnaires conducted at Pasar Bersih Jababeka. The analysis was carried out using both BMC and SWOT models to identify business strengths, weaknesses, opportunities, and threats. The results highlight the importance of maintaining product quality, building customer relationships, and developing marketing and partnership strategies. By applying strategies based on BMC and SWOT analysis, Mochi Daifuku has the potential to grow and compete in the market while contributing to local and national economic development.